Trauma theory and biblical studies - Garber, David G. (Currents in biblical research, 2015)
Since the early 2000s, several scholars have explored the use of trauma theory as an interpretive lens to understand some of the most difficult and painful texts in the Bible. The use of trauma theory does not constitute a method of interpretation but a frame of reference that, when coupled with other methodologies (e.g., psychology, post-structuralism, post-colonialism, refugee studies, etc.), can yield innovative results. While trauma theory has proven useful in the study of exilic texts in particular, scholars have ventured beyond the narrower concern of exilic literature, investigating the use of trauma theory for other portions of the Hebrew Bible and New Testament. The impact of trauma is a significant component of the human condition that lies beneath the production of a wide variety of biblical texts.